2021
DOI: 10.1371/journal.pone.0249400
|View full text |Cite
|
Sign up to set email alerts
|

Digital inequalities in health information seeking behaviors and experiences in the age of web 2.0: A population-based study in Hong Kong

Abstract: Background Inequalities in health information seeking behaviors (HISBs) using mass media and internet websites (web 1.0) are well documented. Little is known about web 2.0 such as social networking sites (SNS) and instant messaging (IM) and experiences of HISBs. Methods We surveyed representative Hong Kong Chinese adults (N = 10143, 54.9% female; 72.3% aged 25–64 years) on frequency of HISBs using traditional sources, internet websites, SNS (e.g., Facebook, Twitter), and IM (e.g., WhatsApp, WeChat) and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Those with tertiary education should be more knowledgeable, and thus was consistent with another unexpected result in the present study that more people who reported having more knowledge of COVID-19 also reported high pandemic fatigue. We previously reported that frequent use of the Internet as a source of COVID-19-related information was associated with psychological distress symptoms 36 , and that health information seeking was more prevalent among younger adults and those with higher education attainment 37 . These findings corroborate with the present results in suggesting that increased exposure to COVID-19-related information, especially among the younger and more educated people, could lead to earlier and stricter compliance of stringent control measures, which when prolonged with uncertainty about when the pandemic would end would lead to earlier and higher pandemic fatigue and related adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Those with tertiary education should be more knowledgeable, and thus was consistent with another unexpected result in the present study that more people who reported having more knowledge of COVID-19 also reported high pandemic fatigue. We previously reported that frequent use of the Internet as a source of COVID-19-related information was associated with psychological distress symptoms 36 , and that health information seeking was more prevalent among younger adults and those with higher education attainment 37 . These findings corroborate with the present results in suggesting that increased exposure to COVID-19-related information, especially among the younger and more educated people, could lead to earlier and stricter compliance of stringent control measures, which when prolonged with uncertainty about when the pandemic would end would lead to earlier and higher pandemic fatigue and related adverse health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that being female and having a higher educational background are the strongest correlates of seeking health information from web-based sources [ 12 , 22 , 29 , 53 , 54 ]. Similar associations have also been suggested with regard to offline health information seeking [ 22 , 29 , 54 ], except for null or inverse associations between education and television exposure [ 38 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the above findings indicate that very little is known about people’s information-seeking behavior toward healthy eating and its potential consequences [ 47 ]. For potential correlates of dietary and nutrition information seeking, this study particularly focused on health literacy [ 48 ], food literacy [ 49 ], and diet quality [ 50 - 52 ], all of which were assessed using validated tools, as well as important sociodemographic variables (sex, age, and education level) [ 12 , 22 , 26 , 28 , 29 , 33 , 36 , 37 , 53 , 54 ]. To achieve sufficient distribution of health literacy, food literacy, and diet quality within the data set, our population consisted of not only the general public but also health professionals allied to nutrition (eg, dietitians, registered dietitians, physicians, and dentists).…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that the percentage of individuals using the internet was positively correlated with online interest in diabetes. Access to technological devices and the internet were shown to be associated with more health-related information-seeking behavior on the internet ( Guo et al, 2021 ; H.Y. Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%